2019
DOI: 10.3844/ajavsp.2019.69.77
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Reproductive Damage Induced by Lead Acetate in Female Guinea Pig (Cavia porcellus): Curative Effects of Hydroethanolic Extract of Spirulina platensis

Abstract: This study was aimed at evaluating the curative effects of Hydroethanolic Extract Of Spirulina platensis (HESP) on the reproductive function of female Guinea pig exposed to oxidative stress. Sixty females, 3-4 months old, weighing 300-400 g were divided into six groups (10 animals/group). The neutral control received distilled water, the negative control was treated with lead acetate at a dose 12 mg/kg.b.w while the positive control was given 12 mg of lead acetate/kg b.w and 100 mg of vitamin C. Groups 4, 5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
2
1
Order By: Relevance
“…Nevertheless, restoration of those stress parameters in cadmium chloride and EEPLM-treated animals suggested that Polygonum limbatum meism could have protective effects against oxidative stress induced by cadmium chloride (37). However, in this study, contrary to the results observed in Deutcheu et al (15), the activity of antioxidant enzymes rather increased in animals exposed to metal only. These results could be justified by the fact that when the stress is moderate, the organism will try to react by over-expressing the level of antioxidant enzymes to try to fight this stress (38,39).…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Nevertheless, restoration of those stress parameters in cadmium chloride and EEPLM-treated animals suggested that Polygonum limbatum meism could have protective effects against oxidative stress induced by cadmium chloride (37). However, in this study, contrary to the results observed in Deutcheu et al (15), the activity of antioxidant enzymes rather increased in animals exposed to metal only. These results could be justified by the fact that when the stress is moderate, the organism will try to react by over-expressing the level of antioxidant enzymes to try to fight this stress (38,39).…”
Section: Discussioncontrasting
confidence: 97%
“…In this study, the level of MDA, SOD, catalase, and total peroxidase activities (Table 5) decreased significantly and became normal in animals co-administered with cadmium chloride and EEPLM compared to the negative control receiving cadmium only. These results are similar to those of Deutcheu et al (15) who reported the same results in lead acetatetreated guinea pigs for the first 30 days at the dose 12 mg/kg bw and then administered 100 mg/kg bw of hydroethanolic extract of Spirulina platensis from the 31st day to the 90th day. Nevertheless, restoration of those stress parameters in cadmium chloride and EEPLM-treated animals suggested that Polygonum limbatum meism could have protective effects against oxidative stress induced by cadmium chloride (37).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Ovary histology is usually used to assess its morphological changes leading to cells and reproductive hormone impairment ( 67 ). Analysis of the micrographs showed damages of ovary of female rabbits solely exposed to heat stress.…”
Section: Discussionmentioning
confidence: 99%